Effects of rabbit-assisted therapy on self-esteem, depression and happiness of abused children. - Tantipisitkul , K,; Pityaratstian , N. (Chulalongkorn Medical Journal, 2023)
Background : Rabbit-assisted therapy is one type of animal-assisted therapy (AAT), which is a field of alternative medicine in Thailand. Animals live closely to human and can be a source of unconditional affection, especially for children with special needs such as abused children. Therefore, it could be used as an alternative therapy to help improve abused children’ mental health in terms of self-esteem, depression, and happiness. Objective : To study effects of rabbit-assisted therapy on self-esteem, depression and happiness of abused children. Design : Experimental research Setting : Lampang Child Development and Rehabilitation Center Sample : Participants were 22 children, who were abused by sexual, physical and emotional. They were 12-18 years old and equally divided by random sampling into two groups: experimental and control group. The 11 participants in the experimental group entered the rabbit-assisted therapy program which included 10 activities in five days. Materials and Methods : The research instruments were: general questionaries, coopersmith self-esteem inventory (CSEI), children depression inventory (CDI), happiness (face scale) and intervention by rabbit-assisted therapy program. Results : After receiving rabbit-assisted therapy, the experimental increased mean scores of self-esteem, decreased depression and increased happiness with no statistically significance. Conclusion : Rabbit-Assisted Therapy had no statistical significance in mean scores of self-esteem, depression and happiness to abused children between experimental group and control group.